ASSESSMENT OF THE EFFECTIVENESS OF A HYBRID SYSTEM OF HEAT AND ELECTRIC SUPPLY FOR A TYPICAL RURAL HOUSE - Uzakov, Norboevich; Kamalov, Bekzod (Innovatsion texnologiyalar, 2023)
Increasing the energy efficiency of modern buildings and structures is an urgent task. To solve the problem, the development of the use of renewable energy sources, which have enormous potential, is considered important. A rational technical solution for the effective use of traditional and renewable energy resources is hybrid energy supply systems for autonomous consumers. In this regard, a technological diagram of a hybrid autonomous heat and power supply system for a typical rural house with a set of solar energy potential lines has been developed in this work. The reduced electrical power of consumers of a typical rural house has been determined, which is in the range of 2.5÷2.74 kW. The results of studies of the characteristics of a solar photovoltaic station with a power of 5.0 kW are presented. The effectiveness of using SPES and SC as part of a hybrid heat and power supply system for a typical rural house is substantiated.